Work Safety in slaughterhouses: general aspects (Research, Society and Development, 2021)
This study aimed at carrying out the characteristics existing in slaughterhouses work scenarios, taking into account the aspects that corroborate to ensure employees' health conditions, such as physical, chemical, biological risks, and, mainly, ergonomic. It is noted that the slaughterhouses have several changes that compromise the physical conditions of those who provide practical actions in these service spaces. The data from this research are seasoned due to issues involving ergonomic aspects such as Work-Related Musculoskeletal Disorders (WRMD) and temperature, humidity, risky materials, noise, extensive workloads, among other factors that compromise, significantly, the health of employees. In short, the scenarios lack changes and improvements in conditions of caring for the well-being of employees, as well as envisioning the need to ensure conditions for improving their materials, proposing a complementation in the training of their workers.